A Fuzzy Evaluation Model Aimed at Smaller-the-Better-Type Quality Characteristics - Kuen-Suan Chen; Tsun-Hung Huang (Mathematics, 2021)
Numerous key components of tool machines possess critical smaller-the-better-type quality characteristics. Under the assumption of normality, a one-to-one mathematical relationship exists between the process quality index and the process yield. Therefore, this paper utilized the index to produce a quality fuzzy evaluation model aimed at the small-the-better-type quality characteristics and adopted the model as a decision-making basis for improvement. First, we derived the 100(1 <semantics>−</semantics><semantics>α</semantics>)% confidence region of the process mean and process standard deviation. Next, we obtained the 100(1 <semantics>−</semantics><semantics>α</semantics>)% confidence interval of the quality index using the mathematical programming method. Furthermore, a one-tailed fuzzy testing method based on this confidence interval was proposed, aiming to assess the process quality. In addition, enterprises’ pursuit of rapid response often results in small sample sizes. Since the evaluation model is built on the basis of the confidence interval, not only can it diminish the risk of wrong judgment due to sampling errors, but it also can enhance the accuracy of evaluations for small sample sizes.